2010 ADA standards for accessible design with commentary (BNi Building News, 2012)
"This all-inclusive guide puts both the '2010 ADA standards for accessible design,' which governs the construction and alteration of places of public use, together with the Department of Justice's 'Guidance on 2010 ADA standards for accessible design," in one complete book" -- Cover p. 4.
Cover title.
Includes index.
Keywords: United States. -- Americans with Disabilities Act of 1990.; Barrier-free design -- Law and legislation -- United States.; Public buildings -- Barrier-free design -- Law and legislation -- United States.; People with disabilities -- Transportation -- Law and legislation -- United States.; Discrimination against people with disabilities -- Law and legislation -- United States.; elektronické knihy; electronic books